Research progress on platinum catalysts for hydrogen-oxygen fuel cells - Chen Yifei (E3S Web of Conferences)
In recent years, China’s fuel cell technology and industry have developed rapidly. However, the high-cost problem caused by the extensive use of Pt-based catalysts remains one of the most important factors restricting its development. As an important component of hydrogen-oxygen fuel cells, platinum-based catalysts are crucial for promoting their application in this field. The development and research of Pt-based catalysts with higher catalytic efficiency are of great significance for promoting the development of fuel cell technology and industry. In this review, some feasible strategies for improving the performance of Pt-based catalysts were summarized based on reducing platinum usage. In addition, the methods and mechanisms of each strategy in enhancing catalytic activity and reducing the amount of platinum catalyst were discussed in detail. At the same time, the shortcomings and challenges faced by this type of catalyst were pointed out, and the future research and application of this type of catalyst were discussed.